Assessment of Serpentine Group Minerals in Soils: A Case Study from the Village of San Severino Lucano (Basilicata, Southern Italy) - Rosalda Punturo; Claudia Ricchiuti; Andrea Bloise (Fibers, 2019)
Naturally occurring asbestos (NOA) is a generic term used to refer to both regulated and un-regulated fibrous minerals when encountered in natural geological deposits. These minerals represent a cause of health hazard, since they have been assessed as potential environmental pollutants that may occur both in rocks and derived soils. In the present work, we focused on the village of San Severino Lucano, located in the Basilicata region (southern Apennines); due to its geographic isolation from other main sources of asbestos, it represents an excellent example of hazardous and not occupational exposure of population. From the village and its surroundings, we collected eight serpentinite-derived soil samples and carried out Differential Scanning Calorimetry (DSC), Derivative Thermogravimetric (DTG) and Transmission Electron Microscopy with Energy Dispersive Spectrometry (TEM-EDS), in order to perform a detailed characterization of serpentine varieties and other fibrous minerals. Investigation pointed out that chrysotile and asbestos tremolite occur in all of the samples. As for the fibrous but non-asbestos classified minerals, polygonal serpentine and fibrous antigorite were detected in a few samples. Results showed that the cultivation of soils developed upon serpentinite bedrocks were rich in harmful minerals, which if dispersed in the air can be a source of environmental pollution.